2008
DOI: 10.1586/14737140.8.3.371
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes for patients with synovial sarcoma of the head and neck

Abstract: Evaluation of: Harb WJ, Luna MA, Patel SR, Ballo MT, Roberts DB, Sturgis EM. Survival in patients with synovial sarcoma of the head and neck: association with tumor location, size, and extension. Head Neck 29, 731-740 (2007). Synovial sarcoma of the head and neck occurs most commonly in males in their third decade of life. Synovial sarcoma of the head is rare, accounting for less than 10% of all head and neck sarcomas. Due to its rarity, there are very few publications on the treatment approach for these tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…Patients usually present a painless slow growing mass during their third and fourth decade of life with associated compressive or infiltrative symptom of surrounding structures, and males tend to be affected more often than females [5]. Consistent with the literature, our five patients were all men and their median age was 35  years (range 22 to 41  years).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Patients usually present a painless slow growing mass during their third and fourth decade of life with associated compressive or infiltrative symptom of surrounding structures, and males tend to be affected more often than females [5]. Consistent with the literature, our five patients were all men and their median age was 35  years (range 22 to 41  years).…”
Section: Discussionsupporting
confidence: 72%
“…Local or distant failure is seen in approximately 80% of cases, and lung metastasis is the usual cause of death in patients with SS of the head and neck [5,15]. Penel et al reported that poor prognostic factors of this tumor include initial metastasis or the presence of lymphadenopathy, absence of surgery and number of surgical procedures [16].…”
Section: Discussionmentioning
confidence: 99%
“…This reflects the use of these two modalities as the mainstay of treatment of SCSHN with chemotherapy more frequently used for large tumors, extensive or recurrent disease, and high-risk sites of presentation such as the skull base or paraspinal neck. 27,29,30,40 Interestingly, neither surgical resection nor radiotherapy was found to have a statistically significant survival advantage using multivariate analysis on either the overall or cohorts separated by size at the 5 cm critical size cutoff. This may reflect the near universal treatment of these tumors with surgical resection and the high propensity for adjuvant radiotherapy for disease control.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies reported that postoperative dose radiotherapy of 50-65 Gy in patients with clear safety margins or microscopic residual tumor was effective in reducing local recurrence, but not survival, [15][16][17] nor the chemotherapy before or after surgery in two different research works. 17,18 Therefore, surgical resection with safe margins is most important; chemoradiotherapy effectiveness remains uncertain.…”
Section: A B Cmentioning
confidence: 99%
“…1 Predictors of worse prognosis for SS have been proposed, such as diameter >5cm, biphasic type, primary site based skull, bone involvement, and positive margins after surgical resection. 8,15 The causes of death in SS are recurrences and distant metastases (lungs after cervical lymph nodes). Although local control is difficult, it has been improved with the development of new surgical techniques.…”
Section: A B Cmentioning
confidence: 99%